Dalihan Na Tolu's Indigenous People's Perception Of Islamic Bank - Rini Hayati Lubis (Iqtishaduna: Jurnal Ilmiah Ekonomi Kita)
This research aims to see the perception of indigenous peoples towards Islamic banks. This research was conducted in the city of Panyabungan. The type of research method used is qualitative with a descriptive approach. Data collection techniques include in-depth interviews with informants from several communities, traditional leaders, and Islamic bank employees. In addition, data was also obtained from several documents and literature related to adat and Islamic banks. This research found that the acceptance of Dalihan Na Tolu indigenous people in Panyabungan was based on Dalihan Na Tolu values through aspects of cognition. The dominant customary values in perceiving Islamic banks in Panyabungan are the values of holong mangalap holong and mangholongi bona bulu. Theoretically, this research can be an additional reference for other researchers and academics who want to see public perceptions of Islamic banks, especially in Panyabungan. Practically, this research can inspire Islamic bank managers, especially in Panyabungan.